2018
DOI: 10.1002/bjs.10761
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-choice experiment to analyse preferences for centralizing specialist cancer surgery services

Abstract: BackgroundCentralizing specialist cancer surgery services aims to reduce variations in quality of care and improve patient outcomes, but increases travel demands on patients and families. This study aimed to evaluate preferences of patients, health professionals and members of the public for the characteristics associated with centralization.MethodsA discrete‐choice experiment was conducted, using paper and electronic surveys. Participants comprised: former and current patients (at any stage of treatment) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 23 publications
2
46
0
Order By: Relevance
“…In another study from the UK, patient's preference to be treated in a high-volume center was based on a lower risk of complications and death, and a better access to multidisciplinary teams. 96 In the same study, patients were willing to travel on average 75 minutes longer in order to reduce their risk of complications by 1%, and over 5 hours longer to reduce risk of death by 1%. According to US studies, for many patients, the influence of outcome data on patients' hospital selection might be overestimated.…”
Section: Patient Perspective On Centralizationmentioning
confidence: 99%
“…In another study from the UK, patient's preference to be treated in a high-volume center was based on a lower risk of complications and death, and a better access to multidisciplinary teams. 96 In the same study, patients were willing to travel on average 75 minutes longer in order to reduce their risk of complications by 1%, and over 5 hours longer to reduce risk of death by 1%. According to US studies, for many patients, the influence of outcome data on patients' hospital selection might be overestimated.…”
Section: Patient Perspective On Centralizationmentioning
confidence: 99%
“…Investigations into patient preferences have revealed that patients with cancer are willing to travel to access specialized surgical care and improve their outcome. However, if there is no increased risk of complications or death, patients prefer to be cared for locally, closer to home, as this often allows for reduced patient‐incurred costs and increased social support from family and friends. In the present study, patients who received adjuvant treatment at a different institution from that where they had surgery travelled a mean of 83·8 km more to undergo pancreatic resection, but no extra distance to receive chemotherapy (26·2 and 22·9 km for the 2 chemotherapy groups).…”
Section: Discussionmentioning
confidence: 79%
“…The study highlights the ability to obtain similar survival for patients by combining surgery for pancreatic adenocarcinoma in specialized centres with decentralized administration of adjuvant chemotherapy, closer to home. This is crucial information for designing patient‐centred and sustainable healthcare delivery strategies and networks of cancer care that support patients to be cared for close to their homes while being offered optimal cancer outcome, along with better social support, enhanced experience and reduced travelling and financial burdens , .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer care, patients were willing to travel 75 min longer to reduce their risk of complications by 1% and over 5 h longer to reduce their risk of mortality by 1%. . The same principle will undoubtedly be true for IBD patients accessing IBD services.…”
Section: General Principles In Ibd Surgerymentioning
confidence: 99%